Sosialisasi : Strategi Akademik Meningkatkan Sitasi Google Scholar - Eko Sudarmanto; M. Imam Muttaqijn; Triana Zuhrotun Aulia; Djuhrijjani Djuhrijjani; Anggraini Soemadi; Nizla Rohaya; Ahmad Ahmad; Muhammad Hendra (Lembaga Pengembangan Kinerja Dosen, 2025)
Citations in Google Scholar serve as a crucial indicator for assessing the impact and relevance of a scientific publication. However, many academics and researchers face challenges in increasing the citation count of their work. This article discusses strategies for enhancing citation numbers through effective dissemination. The methods employed include outreach and training programs, publication in reputable journals, optimization of Google Scholar profiles, and the utilization of academic social media platforms such as ResearchGate and Academia.edu. The findings indicate that a better understanding of publication techniques and scholarly promotion contributes to increased citations. Furthermore, research collaboration and active engagement in academic communities have been shown to expand the reach of scientific work. This article asserts that with the right strategies, academics can enhance the visibility of their research and strengthen their scholarly impact.